2003
DOI: 10.1016/s0005-2736(03)00228-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of proline residues in the NH2-terminal region of the multidrug resistance protein, MRP1 (ABCC1): effects on protein expression, membrane localization, and transport function

Abstract: The Multidrug Resistance Protein, MRP1 (ABCC1) confers drug resistance and transports organic anions such as leukotriene C(4) (LTC(4)) and 17beta-estradiol 17-(beta-D-glucuronide) (E(2)17betaG). Previous studies showed that portions of the first membrane spanning domain (MSD1) and the cytoplasmic loop (CL3) connecting it to MSD2 are important for MRP1 transport function. We have replaced 12 prolines in MSD1 and CL3 with alanine and determined the effects of these substitutions on MRP1 expression and transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
3
19
1
Order By: Relevance
“…Non-membrane associated Pro residues have also been shown to be important for the function of certain ion channels and transporters (38). In a previous study, we replaced 12 Pro residues in MSD1 and CL3 of MRP1 with Ala and found that while several of the resulting mutants showed reduced levels of MRP1 expression, the substitutions had little or no effect on LTC 4 and E 2 17␤G transport (39). These findings are consistent with an interpretation that MSD1 is not critical for conjugated organic anion transport but probably has a role in the stable expression of MRP1 in mammalian cell plasma membranes.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Non-membrane associated Pro residues have also been shown to be important for the function of certain ion channels and transporters (38). In a previous study, we replaced 12 Pro residues in MSD1 and CL3 of MRP1 with Ala and found that while several of the resulting mutants showed reduced levels of MRP1 expression, the substitutions had little or no effect on LTC 4 and E 2 17␤G transport (39). These findings are consistent with an interpretation that MSD1 is not critical for conjugated organic anion transport but probably has a role in the stable expression of MRP1 in mammalian cell plasma membranes.…”
supporting
confidence: 82%
“…The coverslips were then incubated with Alexa Fluor 488 anti-mouse IgG (HϩL) (FabЈ) 2 fragment in 0.1% Triton X-100/PBS containing 2 g ml Ϫ1 propidium iodide and then placed on slides containing 1 drop of Antifade Solution (Molecular Probes, Inc., Eugene, OR). Cells were examined using a Leica TCS SP2 MS multiphoton system confocal microscope (Leica Microsystems, Heidelberg, Germany) as before (39). 4 -Membrane proteins were photolabeled with [ 3 H]LTC 4 essentially as described (40).…”
Section: Transfections Of Mrp1 Expression Vectors In Human Embryonicmentioning
confidence: 99%
“…Alignments of intraspecies homologues and distantly related orthologues reveal little evidence of conserved primary structures suggestive of a common function. Those limited elements identified, such as the cluster of basic amino acids in CL1 and conserved aromatic and Pro residues (Figure 9), seem likely to contribute to determining the orientation and positions of TMs such as TM1 and TM4, respectively (Ito et al, 2003;Koike et al, 2004). Furthermore, conserved tryptophans in MSD0 have been mutated singly, without affecting the transport activity of the protein (Koike et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although the integrity of the cytoplasmic loop immediately after MSD0 is essential for protein processing and activity, it has been concluded that MSD0 is dispensable, at least with respect to trafficking and transport of some substrates. Nevertheless, certain point mutations or deletions in MSD0 decrease or eliminate MRP1 transport activity (Gao et al, 1998;Leslie et al, 2003;Ito et al, 2003) and a recent study of hybrid proteins in which TM1-3 of MSD0 were switched between MRP1 and MRP2 concluded that this NH 2 -terminal region influenced the kinetics of leukotriene C 4 (LTC 4 ) and methotrexate transport by the two homologues (Konno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation